Preparation method and application of nickel-magnesium loaded biochar-based dual-functional material
By preparing nickel-magnesium-loaded biochar-based dual-functional materials, the problems of high transportation costs, high risks and high leakage risks in the storage process of carbon capture and utilization and storage technology in the prior art are solved, which significantly improves CO2 adsorption and conversion performance, enhances the reduction and circulation performance of the material, and achieves efficient flue gas CO2 capture and in-situ methanation.
Patent Information
- Application Number
- CN202411137197.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-08-19
AI Technical Summary
In the prior art, carbon capture and utilization and storage technology has problems such as high transportation costs, high risks and high leakage risks during storage. Most bifunctional materials composed of pure metals and metal oxides have low methanation performance, which limits the further development of integrated carbon capture and in-situ methanization technology.
The preparation method of nickel-magnesium-loaded biochar-based bifunctional material is adopted, and the material is prepared by carbonizing waste biomass material, reacting with Ni(NO3)2·6H2O and Mg(NO3)2·6H2O, and calcining in a nitrogen atmosphere. The magnesium content in the material is basically controlled at about 20%, and the nickel load is regulated between 20%-50%.
It significantly improves the CO2 adsorption and conversion performance of the material, enhances the reduction and circulation performance of the material, improves the methanation performance at low temperatures, and reduces the preparation cost and environmental impact.
Smart Images

Figure CN118719002B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of integrated carbon capture and in-situ utilization, and specifically relates to a preparation method and application of a nickel-magnesium loaded biochar-based dual-functional material. Background Art
[0002] The continuous emission of carbon dioxide is an important factor causing global warming. At present, the key technical means and bottom-line technical guarantee for carbon emission reduction are carbon capture, utilization and storage. Carbon capture, utilization and storage technology mainly consists of carbon dioxide capture, transportation, utilization and storage, and is mainly divided into two categories: carbon capture and utilization (CCU) and carbon capture and storage (CCS). The former can realize the resource utilization of CO2, convert the captured CO2 into fuel or high-value chemicals, and realize the recycling of CO2; while the latter buries the captured unusable CO2 through storage technology, which is currently mainly geological storage and marine storage. Although CCU technology can effectively alleviate excessive carbon emissions, it also has the problems of high cost and high risk. For example, in most carbon capture and utilization technologies, carbon capture and utilization are carried out separately, which requires the addition of a transportation process between the two to connect them. The transportation process not only consumes a lot of manpower and material resources, but also has the risk of leakage. As a supplement to CCU technology, CCS technology can effectively deal with the captured unusable CO2, but after all, the storage does not convert the CO2, but stores it in a specific place. Therefore, there is a certain risk of leakage. Once a leakage occurs, it will lead to large CO2 emissions in a short period of time, leading to more serious consequences.
[0003] Integrated carbon capture and in-situ utilization (ICCU) technology rationally couples the carbon capture stage with the utilization stage, so it can solve many problems existing in CCUS technology. ICCU technology can directly capture and in-situ convert CO2 for utilization without the need for a transportation stage, thus avoiding transportation costs and risks, and has good application prospects. At present, the most common research on ICCU technology includes integrated carbon capture and in-situ methanation (ICCM), integrated carbon capture and in-situ reverse water gas reaction (ICCU-RWGS), and integrated carbon capture and in-situ methane dry reforming (ICCU-DRM). Among them, ICCM technology has a lower reaction temperature than the other two and has more cost advantages. The most critical part of ICCM technology is dual-functional materials (DFM), that is, materials that have both adsorption sites and catalytic sites. Related research has used a mechanochemical method to prepare a batch of Ni / MgO bifunctional materials for ICCM at room temperature. The best performing 80% Ni / MgO has a CO2 capture capacity and CH4 production of 0.37 mmol / g and 0.27 mmol / g at 300°C, a CO2 conversion rate of 73%, and a CH4 selectivity of 100%. However, the methanogenic performance of this pure metal oxide DFM is still low and needs to be further improved.
[0004] Currently, the ICCM performance of most DFMs composed of pure metals and metal oxides is still relatively low, which limits the further development of this technology. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a preparation method and application of a nickel-magnesium loaded biochar-based dual-functional material.
[0006] In order to achieve the above object, the present invention adopts the following technical means:
[0007] The first aspect of the present invention provides a method for preparing a nickel-magnesium loaded biochar-based dual-functional material, the method being as follows:
[0008] The waste biomass material is carbonized at 1000-1200°C under nitrogen atmosphere protection. After the temperature drops to room temperature, the carbonized material is washed in a sulfuric acid solution, then washed with deionized water, filtered and dried to obtain carbonized biochar.
[0009] Ni(NO3)2·6H2O and Mg(NO3)2·6H2O were added into deionized water and stirred to obtain a loading solution;
[0010] Weigh carbonized biochar according to the nickel loading amount of 20%-50% and add it to the loading solution and stir. Transfer the mixed solution to an oil bath and dry it while stirring until the water is completely evaporated;
[0011] The solid material is transferred to a crucible and calcined in a muffle furnace under nitrogen atmosphere at 550°C-650°C for 1.5-2.5 h to obtain a nickel-magnesium loaded biochar-based bifunctional material. In a preferred embodiment of the present invention, the nickel loading of the nickel-magnesium loaded biochar-based bifunctional material is 40%.
[0012] In some embodiments of the present invention, the carbonized biochar is again calcined in a muffle furnace under a nitrogen atmosphere at 550° C.-650° C. for 1.5-2.5 h.
[0013] In some embodiments of the present invention, the concentration of the sulfuric acid solution is 0.4-0.5 mol / L, and the washing time is 10-12 hours.
[0014] In some embodiments of the present invention, during the preparation of the carbonized biochar, the nitrogen atmosphere condition is 100 mL / min, the heating rate is 8-10° C. / min, and is maintained for 0.8-1.2 h.
[0015] In some embodiments of the present invention, during the calcination of the solid material, the nitrogen atmosphere condition is 100 mL / min and the heating rate is 4-5° C. / min.
[0016] In some embodiments of the present invention, the waste biomass material is one of corn cob powder, yellow bamboo powder, wheat straw powder, corn straw powder, or a mixture thereof.
[0017] The second aspect of the present invention provides a nickel-magnesium loaded biochar-based dual-functional material prepared by the method described in the first aspect.
[0018] The third aspect of the present invention provides the application of the nickel-magnesium loaded biochar-based dual-functional material described in the second aspect in integrated flue gas carbon capture and in-situ methanogenesis.
[0019] In some embodiments of the present invention, the application temperature is 300-500°C. In some best embodiments, the application temperature is 400°C.
[0020] Beneficial effects of the present invention
[0021] Compared with the prior art, the present invention has the following beneficial effects: the present invention provides a waste biomass material as a carbon source, and uses Ni(NO3)2·6H2O and Mg(NO3)2·6H2O as chemical materials to provide adsorption site magnesium oxide and catalytic site nickel oxide. The magnesium content in the material is basically controlled at about 20%, and the ratio of nickel to biochar is regulated. The raw materials and preparation costs of the biochar-based bifunctional material are low, the preparation process is simple, and it is environmentally friendly. The prepared biochar-based bifunctional material has a rich pore structure, and the adsorption and conversion of CO2 are significantly improved. At the same time, the incorporation of biochar enhances the reducibility of the prepared bifunctional material, greatly enhancing the methanation performance of the material at low temperature. At the same time, the material also has excellent cycle performance, and can achieve efficient flue gas CO2 capture and in-situ methanation. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The SEM image of 20% Ni@MgO-C prepared in Example 1 is shown;
[0023] Figure 2 The SEM image of 40% Ni@MgO-C prepared in Example 3 is shown;
[0024] Figure 3 The TEM image of 40% Ni@MgO prepared in Comparative Example 1 is shown;
[0025] Figure 4 The EDX mapping diagram of 40% Ni@MgO-C prepared in Example 3 is shown;
[0026] Figure 5 The XRD spectra of the dual-functional materials prepared in Examples 1, 3 and Comparative Example 1 are shown;
[0027] Figure 6 The pore size distribution characteristics of the dual-functional materials prepared in Example 3 and Comparative Example 1 are shown;
[0028] Figure 7 The pore structure parameters of the dual-functional materials prepared in Example 3 and Comparative Example 1 are shown;
[0029] Figure 8 The H2-TPR result diagram of the dual-functional materials prepared in Example 3 and Comparative Example 1 is shown;
[0030] Fig. 9 A comparison chart of CO2 capture and methanation performance of the dual-functional materials prepared in Examples 1-4 is shown;
[0031] Fig.10 A comparison chart of CO2 capture and methanation performance of 40% Ni@MgO-C prepared in Example 3 at different reaction temperatures is shown;
[0032] Fig.11 A comparison chart of CO2 capture and methanation performance of 40% Ni@MgO prepared in Comparative Example 1 at different reaction temperatures is shown;
[0033] Fig.12 The cycling performance of 40% Ni@MgO-C prepared in Example 3 is shown. DETAILED DESCRIPTION
[0034] The following examples are used to demonstrate preferred embodiments of the present invention. It will be appreciated by those skilled in the art that the techniques disclosed in the following examples represent techniques discovered by the inventors that can be used to implement the present invention and therefore can be considered as preferred embodiments of the present invention. However, it will be appreciated by those skilled in the art based on this specification that many modifications may be made to the specific embodiments disclosed herein and still achieve the same or similar results without departing from the spirit or scope of the present invention.
[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs, and the materials cited herein and those cited by them are incorporated by reference. Those skilled in the art will recognize or will learn through routine experimentation that there are many equivalents to the specific embodiments of the invention described herein. Such equivalents are intended to be encompassed by the claims.
[0036] The technical solution of this patent is further described in detail below in conjunction with specific implementation methods.
[0037] A preparation method of a nickel-magnesium loaded biochar-based bifunctional material: waste biomass material is carbonized at 1000°C-1200°C under the protection of a 100 mL / min nitrogen atmosphere, with a heating rate of 8-10°C / min, and maintained for 0.8-1.2 hours. After the temperature drops to room temperature, the carbonized material is placed in a 0.4-0.5 mol / L sulfuric acid solution for washing for 10-12 hours, followed by washing with deionized water, suction filtration and drying to obtain carbonized biochar;
[0038] Ni(NO3)2·6H2O and Mg(NO3)2·6H2O are added to deionized water and stirred evenly to obtain a loading solution; carbonized biochar is weighed according to a nickel loading amount of 20%-50% and added to the loading solution and stirred; the mixed solution is transferred to an oil bath at 90°C and dried while stirring until the water is completely evaporated; in the loading solution, the magnesium content is controlled at about 20%.
[0039] The solid material was transferred to a crucible and calcined in a muffle furnace under a 100 mL / min nitrogen atmosphere at 550°C-650°C with a heating rate of 4-5°C / min for 1.5-2.5 h to obtain a nickel-magnesium loaded biochar-based dual-functional material.
[0040] The waste biomass material is one or a mixture of corn cob powder, yellow bamboo powder, wheat straw powder and corn straw powder.
[0041] The carbonized biochar can be calcined again in a muffle furnace under a nitrogen atmosphere at 550°C-650°C for 1.5-2.5h to enhance thermal stability.
[0042] Example 1
[0043] Weigh 10g corn stalk powder in a crucible, place the crucible in a 1200℃ muffle furnace for the first carbonization, introduce N2 at 100 mL / min, and heat the muffle furnace at a rate of 10℃ / min for 1h. After the temperature drops to room temperature, take out the carbonized black material and place it in a 0.5 mol / L sulfuric acid solution for stirring and washing for 12h. Then wash with deionized water, filter and dry to obtain carbonized biochar.
[0044] 1.4 g of Ni(NO3)2·6H2O and 2.56 g of Mg(NO3)2·6H2O were added to deionized water and stirred for 20 min. Then 1 g of the prepared enhanced biochar was weighed and added to the above solution and stirred for 30 min. After that, the mixed solution was transferred to a 90°C oil bath and dried while stirring until the water was completely evaporated. Finally, the obtained solid material was transferred to a crucible and calcined at 600°C in a muffle furnace protected by a nitrogen atmosphere for 2 h. The nitrogen flow rate in the muffle furnace was 100 mL / min and the heating rate was 5°C / min. When the temperature of the muffle furnace dropped to room temperature, a biochar-based dual-functional material with a nickel oxide content of 20% was obtained, which was recorded as 20%Ni@MgO-C.
[0045] Example 2
[0046] Weigh 10g of yellow bamboo powder in a crucible, place the crucible in a 1200℃ muffle furnace for the first carbonization, introduce N2 at 100 mL / min into the muffle furnace, and heat the muffle furnace at a rate of 10℃ / min for 1h. After the temperature drops to room temperature, take out the carbonized black material and place it in a 0.5 mol / L sulfuric acid solution for stirring and washing for 12h. Then wash with deionized water, filter and dry to obtain the first carbonized biochar.
[0047] Subsequently, the biochar carbonized for the first time was placed in a crucible again and carbonized for the second time at 600°C in a muffle furnace under a nitrogen atmosphere, with a heating rate of 5°C / min and maintained for 2 hours; thus, enhanced biochar with strong thermal stability was obtained.
[0048] Take 2.32 g of Ni(NO3)2·6H2O and 2.56 g of Mg(NO3)2·6H2O and add them to deionized water and stir for 20 min. Then weigh 1 g of the prepared enhanced biochar and add it to the above solution and stir for 30 min. Then transfer the mixed solution to a 90°C oil bath and dry it while stirring until the water is completely evaporated. Finally, transfer the obtained solid material to a crucible and calcine it at 600°C in a muffle furnace protected by nitrogen atmosphere for 2 h. The nitrogen flow rate in the muffle furnace is 100 mL / min and the heating rate is 5°C / min. When the temperature of the muffle furnace drops to room temperature, a biochar-based dual-functional material with a nickel oxide content of 30% is obtained, which is recorded as 30%Ni@MgO-C.
[0049] Example 3
[0050] Weigh 10g of wheat straw powder in a crucible, place the crucible in a 1200℃ muffle furnace for the first carbonization, introduce N2 at 100 mL / min, and heat the muffle furnace at a rate of 10℃ / min for 1h. After the temperature drops to room temperature, take out the carbonized black material and place it in a 0.5 mol / L sulfuric acid solution for stirring and washing for 12h. Then wash with deionized water, filter and dry to obtain the first carbonized biochar.
[0051] Subsequently, the biochar carbonized for the first time was placed in a crucible again and carbonized for the second time at 600°C in a muffle furnace under a nitrogen atmosphere, with a heating rate of 5°C / min and maintained for 2 hours; thus, enhanced biochar with strong thermal stability was obtained.
[0052] 3.78 g of Ni(NO3)2·6H2O and 3.20 g of Mg(NO3)2·6H2O were added to deionized water and stirred for 20 min. Then 1 g of the prepared enhanced biochar was weighed and added to the above solution and stirred for 30 min. After that, the mixed solution was transferred to a 90°C oil bath and dried while stirring until the water was completely evaporated. Finally, the obtained solid material was transferred to a crucible and calcined at 600°C in a muffle furnace protected by a nitrogen atmosphere for 2 h. The nitrogen flow rate in the muffle furnace was 100 mL / min and the heating rate was 5°C / min. When the temperature of the muffle furnace dropped to room temperature, a biochar-based dual-functional material with a nickel oxide content of 40% was obtained, which was recorded as 40%Ni@MgO-C.
[0053] Example 4
[0054] Weigh 10g corn cob powder in a crucible, place the crucible in a 1200℃ muffle furnace for the first carbonization, introduce N2 at 100 mL / min, and heat the muffle furnace at a rate of 10℃ / min for 1h. After the temperature drops to room temperature, take out the carbonized black material and place it in a 0.5 mol / L sulfuric acid solution for stirring and washing for 12h. Then wash with deionized water, filter and dry to obtain the first carbonized biochar.
[0055] Subsequently, the biochar carbonized for the first time was placed in a crucible again and carbonized for the second time at 600°C in a muffle furnace under a nitrogen atmosphere, with a heating rate of 5°C / min and maintained for 2 hours; thus, enhanced biochar with strong thermal stability was obtained.
[0056] Take 6.40 g of Ni(NO3)2·6H2O and 4.32 g of Mg(NO3)2·6H2O and add them to deionized water and stir for 20 min. Then weigh 1 g of the prepared enhanced biochar and add it to the above solution and stir for 30 min. Then transfer the mixed solution to a 90°C oil bath and dry it while stirring until the water is completely evaporated. Finally, transfer the obtained solid material to a crucible and calcine it at 600°C in a muffle furnace protected by nitrogen atmosphere for 2 h. The nitrogen flow rate in the muffle furnace is 100 mL / min and the heating rate is 5°C / min. When the temperature of the muffle furnace drops to room temperature, a biochar-based dual-functional material with a nickel oxide content of 50% is obtained, which is recorded as 50%Ni@MgO-C.
[0057] Comparative Example 1
[0058] 7.75g of Ni(NO3)2·6H2O and 19.23g of Mg(NO3)2·6H2O were added to deionized water and stirred for 20min. Then the mixed solution was transferred to an oil bath at 90℃ and dried while stirring until the water was completely evaporated. Finally, the obtained solid material was transferred to a crucible and calcined at 600℃ in a muffle furnace protected by nitrogen atmosphere for 2 h. The nitrogen flow rate in the muffle furnace was 100 mL / min and the heating rate was 5℃ / min. After the temperature of the muffle furnace dropped to room temperature, a pure metal oxide DFM with a nickel oxide content of 40% was obtained, which was recorded as 40%Ni@MgO.
[0059] Performance Testing and Characterization
[0060] 1. The SEM test results of the dual-functional materials prepared in Example 1, Example 3 and Comparative Example 1 are as follows: Figure 1-3 shown.
[0061] The results show that: Figure 1-2It can be seen that the 20% Ni@MgO-C prepared in Example 1 basically presents regular disc-shaped flakes. This morphology is almost consistent with the morphology of double-layer hydroxide (LDH), and it is speculated that NiMg-LDH is formed during the one-step preparation process. In the 40% Ni@MgO-C prepared in Example 3, there are basically no regular disc-shaped flakes, but a large number of strip-shaped substances appear. This means that when nickel oxide becomes the main component, Ni and Mg cannot form LDH materials. Figure 3 It can be found that the 40% Ni@MgO prepared in Comparative Example 1 without the presence of biochar is basically in the form of stacked particles.
[0062] 2. The TEM test results of the dual-functional material prepared in Example 3 are as follows Figure 4 shown.
[0063] The results show that in the EDS element distribution mapping diagram of 40% Ni@MgO-C prepared in Example 3, the four elements are basically evenly distributed, and the carbon content is significantly lower than the other three elements.
[0064] 3. XRD test and analysis of the crystal structure of the dual-functional materials prepared in Example 1, Example 3 and Comparative Example 1 Figure 5 shown.
[0065] The results show that: from the XRD total spectrum, it can be seen that the dual-functional materials prepared in Example 1, Example 3 and Comparative Example 1 all show characteristic peaks of MgO, NiO and graphite. From the local enlarged view of the characteristic peak of graphite (002), the characteristic peak near 2θ≈25° is very gentle, which means that the carbon still exists mainly in the form of amorphous biochar and no real graphite has been formed. However, the characteristic peaks of the two metal oxides are relatively sharp, indicating that the two metal oxides have high crystallinity. The (200) characteristic peaks of the dual-functional materials prepared in Examples 1, 3 and Comparative Example 1 are between MgO (200) and NiO (200), and the 2θ value approaches the NiO direction as the nickel content increases, which means that an alloy of the two is formed.
[0066] 4. The pore structure of the dual-functional materials prepared in Example 3 and Comparative Example 1 was characterized, and the pore size distribution was as follows: Figure 6 As shown in Figure 2, the pore structure parameters are as follows: Figure 7 shown.
[0067] The results show that: Figure 6 The pore size distribution shows that there are both micropores and mesopores in the 40% Ni@MgO-C prepared in Example 3, but there is almost no pore structure in the 40% Ni@MgO prepared in Comparative Example 1. Figure 7From the specific pore structure parameters, it can be seen that the pore volume and specific surface area of 40% Ni@MgO prepared in Comparative Example 1 are very low, while the 40% Ni@MgO-C prepared in Example 3 has the highest pore volume (0.35 cm 3 / g). It can be seen that the pore structure of the dual-functional material has been significantly improved after the addition of biochar, which will significantly improve the adsorption and conversion of CO2.
[0068] 5. The H2-TPR test results of the dual-functional materials prepared in Example 3 and Comparative Example 1 are as follows: Figure 8 .
[0069] The results show that the 40% Ni@MgO-C prepared in Example 3 has two obvious reduction peaks at 317°C and 615°C, while the 40% Ni@MgO prepared in Comparative Example 1 also has two reduction peaks, but the temperature has shifted significantly to 461°C and 852°C, respectively. This shows that the reducibility of the dual-functional material is greatly enhanced after the addition of biochar, and it is speculated that the methanogenic performance of the 40% Ni@MgO-C prepared in Example 3 will be stronger at low temperatures.
[0070] 6. The CO2 adsorption performance and methanation performance of the dual-functional materials prepared in Examples 1-4 and Comparative Example 1 under different working conditions were tested using a fixed bed adsorption breakthrough experiment.
[0071] The specific test process is as follows:
[0072] Weigh about 200 mg of the bifunctional material and place it in a fixed bed reactor, then raise the temperature to the target reduction temperature under 100 mL / min of pure nitrogen. Then switch the pure nitrogen to a 40% H2 mixed gas with the same flow rate to reduce the bifunctional material. After reduction, switch the gas to pure nitrogen and purge for 20 minutes until the hydrogen concentration is 0. Adjust the reactor temperature to the target temperature to start the ICCM test. Pass 100 mL / min of 10% CO2 mixed gas to start CO2 capture for 20 minutes. Then switch the gas to a 10% H2 mixed gas with the same flow rate for a 30-minute CO2 in-situ methanation reaction. After the reaction, switch the gas to pure N2 for a 20-minute purge.
[0073] The CO2 adsorption and desorption amount and conversion rate, CO generation amount, CH4 generation amount and selectivity can be calculated by the following calculation formula.
[0074]
[0075] Among them, q adCO2 (mmol / g) is the adsorption amount, Q is the total gas flow rate (mL / min), C in (mg / m 3 ) and C outare the CO2 inlet and outlet mass concentrations, respectively, and m is the DFM mass. X (mmol / g) is the amount of production, C X (mg / m 3 ) is the mass concentration, where X is one of CO, CH4 and desorbed CO2. Mr is the relative molecular mass of the corresponding molecule. η is the CO2 conversion rate, and XCH4 is the CH4 selectivity.
[0076] The dual-functional material was reduced at 500°C and then reacted at 400°C. The test data are shown in Table 1.
[0077] Table 1 Test results of the reaction of dual-function materials prepared in Examples 1-4 and Comparative Example 1 at 400°C
[0078]
[0079] (1) CO2 capture and methanogenesis performance of the dual-functional materials prepared in Examples 1-4 Fig. 9 shown.
[0080] Depend on Fig. 9 It can be seen that with the increase of the loaded nickel content, the CO2 adsorption and desorption amount is decreasing, while the conversion rate has been increasing. With the increase of nickel content in the range of 20%-40% loading, both the methane production and selectivity are greatly increased. The methane production of 40%Ni@MgO-C prepared in Example 3 is as high as 0.51mmol / g, and the methane selectivity is as high as 94.41%. When the nickel content reaches 50%, the methane production also decreases due to the decrease in CO2 adsorption. We also tested the ICCM performance of the bifunctional material prepared in Comparative Example 1 under the same conditions and compared it with the bifunctional materials prepared in Examples 1-4 as shown in Table 1. It can be seen from Table 1 that except for the bifunctional material prepared in Example 1, which has a slightly lower performance than the bifunctional material prepared in Comparative Example 1, the performance of the bifunctional materials prepared in Examples 2-4 is significantly stronger than that of the bifunctional material prepared in Comparative Example 1. Generally speaking, the four bifunctional materials prepared in Examples 1-4 all exhibit certain ICCM performance, among which the material with a nickel content of 40% has the best performance.
[0081] (2) CO2 capture and methanogenesis performance of 40% Ni@MgO-C prepared in Example 3 at different reaction temperatures Fig.10 shown.
[0082] The maximum adsorption amount of 40%Ni@MgO-C at 300°C is 1.03mmol / g. With the increase of adsorption temperature, the CO2 adsorption and desorption amount gradually decreases. The CO2 conversion rate of 40%Ni@MgO-C increases with the increase of reaction temperature, and the conversion rate at each temperature is always higher than that of 40%Ni@MgO prepared in Comparative Example 1. The optimal reaction temperature of 40%Ni@MgO-C is 400°C. When the temperature is lower than 400°C, the outputs of CH4 and CO are both low due to the low CO2 conversion rate. When the temperature is higher than 400°C, although the CO2 conversion rate is high, the total output of CO and CH4 is also decreasing due to the low CO2 adsorption amount. At this time, the main factor limiting the methanation performance is the CO2 adsorption process. In summary, it can be seen that biochar-based bifunctional materials can exhibit certain ICCM performance at 300-500°C, with 400°C being the optimal reaction temperature.
[0083] (3) CO2 capture and methanogenesis performance of 40% Ni@MgO prepared in Comparative Example 1 at different reaction temperatures Fig.11 shown.
[0084] It can be seen that the CO2 adsorption and desorption amount of 40%Ni@MgO also decreases with the increase of adsorption temperature, and the CO2 adsorption and desorption amount at each temperature is basically consistent with that of 40%Ni@MgO-C. The CO2 conversion rate of 40%Ni@MgO prepared in Comparative Example 1 increases with the increase of reaction temperature. The methane production of 40%Ni@MgO at 400°C is 0.13mmol / g, and the methane selectivity is 61.38%, which is similar to the performance of pure metal nickel-magnesium DFM reported so far. With the increase of reaction temperature, the total production of CO and CH4 of 40%Ni@MgO continues to increase; the methane production is 0.15mmol / g when the reaction temperature rises to 500°C, but the CO production is as high as 0.31mmol / g at this time, and the methane selectivity is only 32.94%. The change pattern of total production with temperature is different from that of 40%Ni@MgO-C, because the main factor limiting the production at this time is catalytic performance rather than adsorption performance. From Fig.10 and 11 It can be seen that the addition of biochar has little effect on the CO2 adsorption, but it has a huge effect on the subsequent CO2 in-situ methanation performance. At the same temperature, the methane yield and selectivity of 40% Ni@MgO are much lower than those of 40% Ni@MgO-C, indicating that the addition of biochar greatly enhances the methanation performance. On the one hand, the addition of biochar enhances the catalytic activity of DFM and greatly improves the CO2 conversion rate at relatively low temperatures; on the other hand, it inhibits the reverse water gas shift reaction and greatly improves the CH4 selectivity.
[0085] (4) The cycle performance of 40% Ni@MgO-C prepared in Example 3 is as follows Fig.12 shown.
[0086] From the five cycle tests, it can be found that the adsorption and desorption amount and conversion rate of CO2 by 40% Ni@MgO-C are relatively stable, without obvious decline, the methane production basically remains between 0.51-0.53 mmol / g, and the methane selectivity also remains at around 94%, showing excellent cycle performance.
[0087] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as references separately. In addition, it should be understood that after reading the above teachings of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined in the present application.
Claims
1. A method for preparing a nickel-magnesium loaded biochar-based dual-functional material, characterized in that: Here’s how: The waste biomass material is carbonized at 1000-1200°C under nitrogen atmosphere protection. After the temperature drops to room temperature, the carbonized material is washed in a sulfuric acid solution, then washed with deionized water, filtered and dried to obtain carbonized biochar. The carbonized biochar is calcined again in a muffle furnace under a nitrogen atmosphere at 550° C. to 650° C. for 1.5 to 2.5 h; Ni(NO3)2·6H2O and Mg(NO3)2·6H2O were added into deionized water and stirred to obtain a loading solution; Weigh the re-calcined carbonized biochar according to the nickel loading amount of 40%-50% and add it to the loading solution and stir. Transfer the mixed solution to an oil bath and dry it while stirring until the water is completely evaporated; The solid material is transferred to a crucible and calcined in a muffle furnace under nitrogen atmosphere at 550°C-650°C for 1.5-2.5h to obtain a nickel-magnesium loaded biochar-based dual-functional material.
2. The method for preparing a nickel-magnesium loaded biochar-based dual-functional material according to claim 1, characterized in that: The concentration of the sulfuric acid solution is 0.4-0.5 mol / L, and the washing time is 10-12 hours.
3. The method for preparing a nickel-magnesium loaded biochar-based dual-functional material according to claim 1, characterized in that: During the preparation of the carbonized biochar, the nitrogen atmosphere condition is 100 mL / min, the heating rate is 8-10° C. / min, and is maintained for 0.8-1.2 h.
4. The method for preparing a nickel-magnesium loaded biochar-based dual-functional material according to claim 1, characterized in that: During the calcination of the solid material, the nitrogen atmosphere condition was 100 mL / min and the heating rate was 4-5°C / min.
5. A method for preparing a nickel-magnesium loaded biochar-based dual-functional material according to any one of claims 1 to 4, characterized in that: The waste biomass material is one of corn cob powder, yellow bamboo powder, wheat straw powder, and corn straw powder, or a mixture thereof.
6. A nickel-magnesium loaded biochar-based dual-functional material prepared by the method described in any one of claims 1 to 5.
Citation Information
Patent Citations
Multi-core-shell structure nickel-based catalyst applied to carbon dioxide reforming reaction, and preparation method and use of multi-core-shell structure nickel-based catalyst
CN110732328A
Carbon dioxide capture and conversion integrated bifunctional catalyst as well as preparation method and application thereof
CN114377679A
KR20220091818A